Guidelines for assessment of affect-related constructs - Williams, David M.; Rhodes, Ryan E. (Frontiers in Psychology, 2023)
Research on affect-related constructs as determinants of health behavior is increasing. The Affect and Health Behavior Framework (AHBF) provides a schematic structure to label, organize, and integrate affect-related constructs. To further facilitate research and theory development in health behavior science, the purpose of the present paper is to provide a critical review and guidelines for assessment of the affect-related constructs in the AHBF. The paper is organized based on the categories of constructs in the AHBF: Affective response to health behavior, incidental affect, affect processing, and affectively charged motivation. Future research should work toward parsing constructs where possible as well as identifying overlap. Researchers are advised to consider conceptual underpinnings and methodological nuances when assessing affect-related constructs in order to build a cumulative science of affective determinants of health behavior.